Knowledge and Teaching Competencies of Physical Education Teachers on Students with Special Needs in the Central Region, Ghana - Kodwo Owusu; Daniel Apaak; Charles Domfeh; Alexander Kweku Eshun (Baltic Journal of Sport and Health Sciences)
Background: This research investigated the inclusion of students with special needs during Physical Education lessons in the Central Region, Ghana. Many learners only observe during Physical Education lessons because the teachers simply ignore them or are challenged with how to integrate them into the lessons. There were also challenges with the nature of the facilities and equipment available for lesson delivery.